PENERAPAN AKUNTANSI MANAJEMEN SEBAGAI ALAT PENGAMBILAN KEPUTUSAN DI BOLLY DEPARTEMEN STORE SILA KABUPATEN BIMA - Afdatul Ramadhan emi sumiati; Abd Salam; Ainun Arizah (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2025)
This study aims to analyze the implementation of management accounting as a tool supporting managerial decision-making at Bolly Department Store Sila, Bima Regency. The research uses a qualitative case study approach through in-depth interviews, observation, and documentation involving the store owner, operational manager, administrative staff, and warehouse employee. The findings indicate that management accounting plays an important role in planning, cost control, and performance evaluation. Financial and non-financial information—summarized in daily, weekly, and monthly reports—is utilized as the basis for decisions related to product procurement, promotional strategies, workforce allocation, and operational efficiency. Although the recording system remains simple and is mostly conducted using Microsoft Excel, the information produced is relevant, timely, and actively used by management. These results demonstrate that management accounting does not need to be complex but must align with organizational conditions, consistent with contingency theory. This study provides theoretical and practical contributions to the development of management accounting practices among small and medium-sized enterprises in regional areas.